Reflections from a school councillor inspired by Korczak’s heritage - Kurcińska, Lidia (Studia Krytyczne/Critical Studies, 2019)
In this short article inspired by Korczak’s life and works I want to present my opinions and views as a teacher and a tutor, working with today’s youngsters. Can Korczak’s thoughts truly inspire today’s generation of teachers? Is there a chance to apply them in today’s school? All my thoughts and reflections are both from participant’s and observer’s point of view. In this paper I will refer to selection of Korczak’s works (such as his getto diary) and their academic interpretations. I will discuss issues of children’s democracy reflected in educational practice, utilize children’s rights perspective looking into processual understanding of oneself as an educator and as a human being, before trying to find deeper understanding of a child or a youth. I will tie Korczak’s ideas with my personal experiences, stressing out their potentiality for a more sensitive and empathetic school environment, where youths of today are already the adults of tomorrow, living here and now.